ANALISIS KONDISI SATWA LIAR DI AREAL PERTAMBANGAN BATUBARA (PT. JORONG BARUTAMA GRESTON) - Edy Kurniawan; Abdi Fithria; Badaruddin - (Universitas Lambung Mangkurat, 2021)
This study aims to inventory the types of wildlife in various land covers in the coal mining area of PT. Jorong Barutama Greston and analyzed the diversity, evenness and relative frequency of wildlife in various land covers in the mining area of PT. Jorong Barutama Greston. Animals are observed by a combination of circle and exploration methods. The observation results of wildlife found in 7 locations are 1217 individuals with 90 species from 45 families in PT. JBG. The highest diversity index values are found in riparian forests and the lowest diversity values are found in reclamation sites in 2016 from all observations of species of aves and mammals, for the highest diversity reptile category found in riparian forests and the lowest in Reclamation 2005. Evenness values are inversely proportional to diversity values, the higher the value of diversity the lower the value of evenness and vice versa the lower the value of diversity the higher the value of evenness. This is because the number of species found differs greatly from the number of individuals that are spread unevenly at each observation location. Wildlife that has the highest relative frequency value with a value of 100% is found in the type of aves, striped bird (Rhipidura javanica), sriganti honey bird (Nectarinia jugularis), coconut honey bird (Anthreptes malacensis), king sepah honey bird (Aethopyga siparaja) and for sriganti honey birds (Nectarinia jugularis), coconut honey birds (Anthreptes malacensis), king sepah honey birds (Aethopyga siparaja) and for sriganti honey birds (Nectarinia jugularis), coconut honey birds (Anthreptes malacensis) mammals are coconut squirrels (Callosciurus notatus).Keywords: Analysis; Land cover; Diversity; Relative frequency